Pengaruh Penerapan Metode Bercerita Melalui Buku Cerita Bergambar Terhadap Konsentrasi Belajar Anak - Yuniarti, Yuniarti; Rafikah, Noviana; Sutrisno, Sutrisno (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2023)
This research is based on children's difficulty concentrating in learning. This research aims to determine the effect of learning concentration on children aged 5-6 years by using the storytelling method through picture story books. The implementation of the learning method used using the storytelling method without using interesting and varied media, makes students less interested and enthusiastic in learning activities. This causes researchers to be interested in providing storytelling methods through picture story books to help develop children's learning concentration. This research uses a quantitative experimental method with a Pre-Exspremental Design (non-design) design. Sampling used scoring techniques on pre-test and post-test checklist sheets, the research sample consisted of class B4 with a total of 17 children. Data collection techniques using observation sheets, interviews and documentation. This research uses data analysis techniques, normalization and hypothesis testing, t test (real level) using SPSS version 25. The results of data analysis and hypothesis testing that have been carried out can be seen from the sig value (2-tailed) = 0.000 while 0.05 (0.00 <0.05) then Ha is accepted and Ho is rejected with a comparison of the average pre-test 5, and post-test 8.23. It can be concluded that the learning concentration of class B4 children has a significant influence on the storytelling method through picture story books on children's learning concentration at the Pembina South Pontianak State Kindergarten.